(untitled) (International Journal of Engineering and Computer Science, 2017)
In this paper, we made a comprehensive simulation study to evaluate the performance of a multi-user Wideband CDMA wireless communication system. The 2-by-1 spatially multiplexed ½-rated Convolutionally encoded system under investigation incorporates Alamouti space-time block coding scheme with utilization of Walsh Hadamard codes and various digital modulations (BPSK, DPSK, QAM, QPSK and 8PSK). In our study, MATLAB based computer programs have been developed to process the synthetically generated multi-user bit streams and text messages under Additive white Gaussian noise (AWGN) and Raleigh fading channels. The simulation results elucidate that a significant improvement of system performance is achieved with BPSK digital modulation scheme at a comparatively low signal to noise ratios. It has been anticipated from the simulation study that the implementation of Walsh Hadamard is highly effective to discriminate the data (Synthetically generated/text) of individual users.